Implementation of Mukhabarah in Productive Waqf Management to Improve Social Welfare in Bireuen - Fitri, Mulyana; Marliyah, Marliyah; Arif, Muhammad (Journal La Sociale, 2024)
This research examines the implementation of mukhabarah in the management of productive waqf to improve social welfare in Bireuen. Mukhabarah, as a profit-sharing system in agriculture, allows cooperation between nadzir (waqf managers) and cultivators to manage waqf land productively. The research results show that mukhabarah can increase land productivity, cultivator income, and the quality of life of the community. The social impacts of this system include reducing unemployment, increasing agricultural skills, and strengthening social ties. However, the implementation of mukhabarah faces challenges such as a lack of understanding and skills of nadzir, unsupportive regulations, and limited access to capital and technology. The role of the government and Islamic financial institutions is very important in supporting and overcoming these challenges. By increasing the capacity of nadzir and cultivators, developing supportive regulations, facilitating access to capital and technology, infrastructure and market support, as well as collaboration between stakeholders, it is hoped that the implementation of mukhabarah can run more effectively and provide optimal benefits for community welfare.